1998
DOI: 10.1111/j.1439-0426.1998.tb00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturity, spawning and sex ratio of pike perch, Stizostedion luciopevca (L.), in two Bulgarian reservoirs as compared to other European habitats

Abstract: The reproductive biology of pike perch, Stizostedion lucioperca (L.), was studied in two Bulgarian reservoirs; results were compared with data from other water bodies within its natural European range. Age at first maturity, onset of spawning, and sex ratio were determined and found to be different between the populations of the two reservoirs. Fish from the cooling reservoir of a power station matured earlier at smaller sizes because of elevated temperatures; this also resulted in an increased proportion of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 2 publications
2
16
0
Order By: Relevance
“…However, elsewhere both mono-and dimorphism has been noted for pikeperch. The onset length and age at maturity is generally lower in males than in females (Svärdson and Molin, 1968;Lehtonen and Miina, 1988;Raikova-Petrova and Zivkov, 1998). In two Finnish lakes showing normal growth no differences were found between sexes in length at age (Lappalainen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, elsewhere both mono-and dimorphism has been noted for pikeperch. The onset length and age at maturity is generally lower in males than in females (Svärdson and Molin, 1968;Lehtonen and Miina, 1988;Raikova-Petrova and Zivkov, 1998). In two Finnish lakes showing normal growth no differences were found between sexes in length at age (Lappalainen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In warmer environments maturity is reached already at age 1 or age 2 (Karabatak, 1992;Raikova-Petrova and Zivkov, 1998;Toujani and Kraiem, 2002;Poulet et al, 2004). Normally fast growing populations have individuals maturing at an earlier age and larger size (Heibo and Vøllestad, 2006), while a slow growing population should include individuals maturing at a small size as it was found in Lake Sahajärvi.…”
Section: Discussionmentioning
confidence: 99%
“…The review of maturity data of pikeperch in the Baltic Sea and its drainage area (Table 1), excluding those references which have already been presented by Raikova‐Petrova & Zivkov (1998), showed that (i) males become mature at smaller size and are younger than females and (ii) the maturity is reached at younger age and at smaller size in southern populations than in northern populations. The youngest known age for maturity is during the second growing season (Raikova‐Petrova & Zivkov 1998). Raikova‐Petrova & Zivkov (1998) also noted the earlier maturity of males by 1–2 years in 26 eastern pikeperch populations.…”
Section: Maturity and Maturation Cyclementioning
confidence: 98%
“…Recent reviews of pikeperch have dealt with general biology (Craig 1987; Sonesten 1991; Lehtonen et al. 1996) or special aspects of reproduction (Zivkov & Petrova 1993; Raikova‐Petrova & Zivkov 1998). Here our intent is focused more on general reproduction by covering the whole distribution area.…”
Section: Introductionmentioning
confidence: 99%
“…The range of optimum temperatures is taken as identical to that of the juveniles (optimum between 27°C and 30°C). The temperatures for the beginning and end of reproduction have been reported by seven authors, with boundary values of 3°C in Eastern Europe and 26°C in Finland (Zhdanova, 1966;Alabaster and Lloyd, 1982;Raikova-Petrova and Divkov, 1998). All other references place the lower boundary temperature at around 6-8°C (Fishbase; Hokanson, 1977;Deelder andWillemsen, 1964 in Gillet, 1989;Gillet, 1989;Mann, 1996;Raikova-Petrova and Divkov, 1998 in Bulgaria;EIFAC, 1969in Küttel et al, 2002Fontell et al, 2004 in Finland;Teletchea et al, 2009b) and the upper boundary value at 20°C (Hokanson, 1977;Gillet, 1989;Mann, 1996;EIFAC, 1969in Küttel et al, 2002Fontell et al, 2004 in Finland).…”
Section: Pike-perch (Sander Lucioperca)mentioning
confidence: 99%